Physical exercise and anti-inflammatory agents in an animal model of seizures: insights into lipid peroxidation and antioxidant activity - Rosa, Gabriel de Lima; Guzzo, Edson Muller; Nunes, Silvia Elisandra Bitello; Faverzani, Jéssica Lamberty; Padilha, Rafael Bremm; Lima, Amanda Muliterno Domingues Lourenço de; Barbosa, Brayan Braz; Vargas, Carmen Regla; Siqueira, Ionara Rodrigues; Simon Coitinho, Adriana (Journal of Health & Biological Sciences, 2025)
A previous study revealed the protective effect of an aerobic exercise protocol on behavioral and inflammatory aspects in an animal model of epileptic seizures. The previously collected samples in that investigation were now analyzed from the perspective of oxidative stress. Five experimental groups of Wistar rats were used (sedentary, diazepam, two physical exercise groups, and naive). Analyzes of lipid peroxidation, sulfhydryl content levels, and quantification of reduced glutathione were performed in the cortical and hippocampal tissues of the animals. There was no change in any parameter in any of the analyzed tissues.